Damage‐induced regeneration of the intestinal stem cell pool through enteroblast mitosis in the Drosophila midgut. (11th August 2022) - Tian, Aiguo; Morejon, Virginia; Kohoutek, Sarah; Huang, Yi‐Chun; Deng, Wu‐Min; Jiang, Jin
Abstract: Many adult tissues and organs including the intestine rely on resident stem cells to maintain homeostasis and regeneration. In mammals, the progenies of intestinal stem cells (ISCs) can dedifferentiate to generate ISCs upon ablation of resident stem cells. However, whether and how mature tissue cells generate ISCs under physiological conditions remains unknown. Here, we show that infection of the Drosophila melanogaster intestine with pathogenic bacteria induces entry of enteroblasts (EBs), which are ISC progenies, into the mitotic cycle through upregulation of epidermal growth factor receptor (EGFR)‐Ras signaling. We also show that ectopic activation of EGFR‐Ras signaling in EBs is sufficient to drive enteroblast mitosis cell autonomously. Furthermore, we find that the dividing enteroblasts do not gain ISC identity as a prerequisite to divide, and the regenerative ISCs are produced through EB mitosis. Taken together, our work uncovers a new role for EGFR‐Ras signaling in driving EB mitosis and replenishing the ISC pool during fly intestinal regeneration, which may have important implications for tissue homeostasis and tumorigenesis in vertebrates. Synopsis: The regenerative cell populations replenishing the intestinal epithelium upon tissue damage remain debated. This genetic tracing study reports a role for enteroblasts (EBs), an intermediate cell type derived from intestinal stem cells (ISCs), as an alternative source of midgut regeneration upon bacterial infection. Bacterial infection with Pseudomonas entomophila or Erwinia carotovora results in EB entry into mitosis in the fly midgut. EGFR‐Ras signaling in EBs is required and sufficient to induce EB mitosis. Bacterial infection induces generation of ISC‐like cells from EBs in an EGFR‐Ras signaling‐dependent manner. EB division generates regenerative and functional ISCs in vivo . Abstract : Enteroblasts replenish the fly intestinal epithelium upon bacterial infection in an EGFR‐Ras signaling‐dependent manner.